Osmotic myelinolysis: literature review and case report - Rutkauskaitė , G.; Klimašauskienė , A. (Neurologijos seminarai, 2018)
Central pontine myelinolysis is described as osmotic myelinolysis syndrome which usually occurs as a consequence of rapid correction of hyponatremia. Pontine myelinolysis is divided into central pontine myelinolysis and extrapontine myelinolysis. Hyponatremia is commonly found in patients with chronic alcoholism and malnutrition and can be caused by liver diseases, the syndrome of inappropriate antidiuretic hormone secretion, as well as adrenal insufficiency and iatrogenic disorders. There are several pathophysiologic mechanisms that explain the development of osmotic myelinolysis. A biphasic clinical course is characteristic. The primary symptoms are encephalopathy and/or seizure attacks due to hyponatremia followed by regeneration during normonatremia and, after several days, a deterioration may manifest with focal neurological symptoms, mental and behavioral disorders. The earliest intrinsic brain changes can be seen in the MRT DWI images. There are no approved recommendations for the treatment of osmotic myelinolysis, however, the literature describes four successful cases when treating patients with thyrotropin-releasing hormone, plasmapheresis therapy, corticosteroids and intravenous immunoglobulins. Osmotic myelinolysis can be prevented by increasing the serum sodium concentration by 4 to 6  mmol/L in a 24-hour period and the maximum rate of correction should be 8 mmol/L in other 24-hour periods. With proper recognition and therapy, the outcomes of osmotic myelinolysis can improve. We present a case report of a 30-year old male patient with parkinsonian syndrome when magnetic resonance imaging confirmed extrapontine myelinolysis.
Keywords: osmotic myelinolysis; central pontine myelinolysis; extrapontine myelinolysis; hyponatremia